2017
DOI: 10.1002/chem.201703660
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanotransducers in Biomedicine

Abstract: Owing to their abilities to identify diseased conditions, to modulate biological processes, and to control cellular activities, magnetic nanoparticles have become one of the most popular nanomaterials in the biomedical field. Targeted drug delivery, controlled drug release, hyperthermia treatment, imaging, and stimulation of several biological entities are just some of the several tasks that can be accomplished by taking advantage of magnetic nanoparticles in tandem with magnetic fields. The huge interest towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
0
11
0
1
Order By: Relevance
“…[ 12,13 ] The deep penetration of magnetic fields within the human body, together with the possibility of targeting MNPs to specific tissues, have enabled minimally invasive, local, and remotely activated heating showing high efficacy at the in vitro and in vivo levels. [ 14–23 ] Clinical trials have shown the efficacy of MHT to treat solid tumors, as well as to increase the usefulness of chemotherapy by enhancing drug permeability of cancer tissues. [ 24,25 ] Reaching high standards of efficacy and selectivity in MHT treatments requires full control over the remote heating process, which means precise localization of the MNPs and real‐time thermal feedback into the treated tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12,13 ] The deep penetration of magnetic fields within the human body, together with the possibility of targeting MNPs to specific tissues, have enabled minimally invasive, local, and remotely activated heating showing high efficacy at the in vitro and in vivo levels. [ 14–23 ] Clinical trials have shown the efficacy of MHT to treat solid tumors, as well as to increase the usefulness of chemotherapy by enhancing drug permeability of cancer tissues. [ 24,25 ] Reaching high standards of efficacy and selectivity in MHT treatments requires full control over the remote heating process, which means precise localization of the MNPs and real‐time thermal feedback into the treated tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Although targeted delivery by nanocarriers can increase the amount of drug at the brain level, the accumulation to the tumor site can however result quite limited [25]. A solution for focusing drug-loaded nanoparticles to a specific area of the organism is offered by the exploitation of magnetically responsive nanostructures, that can be directed toward target sites through the use of magnetic fields produced, for example, by external static sources like permanent magnets [26]. In this view, the present study proposes a nanotechnological solution to increase the possibilities of treatment against GBM.…”
mentioning
confidence: 99%
“…On one side, we can take advantage of the lipid-based nanoparticle features, such as the high drug payload, the better targeting, and the improvement in terms of systemic toxicity of the treatment. On the other side, we could benefit from the magnetic nanoparticle characteristics: [ 128 ] they can be used for imaging as contrast agents in magnetic resonance imaging (MRI), [ 129 ] to perform physical targeting, [ 130 ] and to induce magnetic hyperthermia [ 131 ] applying an alternate magnetic field (AMF), and thus inducing a local temperature increment. This increased temperature can be beneficial for different purposes, such as the controlled drug release using temperature-sensitive nanomaterials.…”
Section: Lipid-based Nanoparticles Combined With Magnetic Nanoparticlmentioning
confidence: 99%